2015
DOI: 10.1111/pin.12322
|View full text |Cite
|
Sign up to set email alerts
|

A case of intraductal tubulopapillary neoplasm of pancreas with severe calcification, a potential pitfall in diagnostic imaging

Abstract: We experienced a case of intraductal tubulopapillary neoplasms (ITPN) of the pancreas with severe calcification, which complicated image diagnosis. A pancreas head tumor was detected in a Japanese female in her 50s. Early enhancement by contrast-enhanced CT and coarse calcification suggested a neuroendocrine tumor, although the obstruction and dilation of the main pancreatic duct appeared to be an intraductal tumor. An endoscopic ultrasound-guided fine needle aspiration biopsy specimen revealed adenocarcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Recently, Ahls et al also reported an ITPN with clear cell phenotype 29 . Rare cases of ITPN with extensive calcification 35 or stromal osseous and cartilaginous metaplasia 28 have also been described, similar to one of our cases with calcification and bone formation. Nuclear atypia varies from moderate to marked, and mitotic figures are easily identified.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, Ahls et al also reported an ITPN with clear cell phenotype 29 . Rare cases of ITPN with extensive calcification 35 or stromal osseous and cartilaginous metaplasia 28 have also been described, similar to one of our cases with calcification and bone formation. Nuclear atypia varies from moderate to marked, and mitotic figures are easily identified.…”
Section: Discussionsupporting
confidence: 84%
“…After applying our inclusion criteria, 68 articles were included in the systematic review (Figure S1). 11–78 …”
Section: Resultsmentioning
confidence: 99%
“…16 Rare ITPN cases have coarse calcification that can be mistaken for a neuroendocrine tumor. 17 However, concurrent obstruction and dilation of the main pancreatic duct would suggest an intraductal lesion. Knowledge about fluorodeoxyglucose-positron emission tomography findings for ITPN is limited.…”
Section: Imaging Studiesmentioning
confidence: 99%